2020
DOI: 10.3390/su12125207
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Water Quality Conditions Associated with Livestock Grazing, Recreation, and Rural Residences in Mixed-Use Landscapes

Abstract: Contamination of surface waters with microbial pollutants from fecal sources is a significant human health issue. Identification of relative fecal inputs from the mosaic of potential sources common in rural watersheds is essential to effectively develop and deploy mitigation strategies. We conducted a cross-sectional longitudinal survey of fecal indicator bacteria (FIB) concentrations associated with extensive livestock grazing, recreation, and rural residences in three rural, mountainous watersheds in Califor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…A growing number of studies examining climate effects on water quality have found E. coli levels in streams and other waterbodies are correlated with ambient air temperature (Whitman & Nevers, 2008; Xu et al., 2019). Maximum bacterial concentrations often occur during the warmest part of the year (Cha et al., 2016; Derose et al., 2020), potentially driven by the ability of E. coli to reproduce rapidly in warmer waters (Guber et al., 2015). Our study suggests that this might be happening across our sites, and that having cattle present during the warmest part of the year when levels of E. coli are at their peak, can increase the chance of violating regulatory water quality benchmarks.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies examining climate effects on water quality have found E. coli levels in streams and other waterbodies are correlated with ambient air temperature (Whitman & Nevers, 2008; Xu et al., 2019). Maximum bacterial concentrations often occur during the warmest part of the year (Cha et al., 2016; Derose et al., 2020), potentially driven by the ability of E. coli to reproduce rapidly in warmer waters (Guber et al., 2015). Our study suggests that this might be happening across our sites, and that having cattle present during the warmest part of the year when levels of E. coli are at their peak, can increase the chance of violating regulatory water quality benchmarks.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were placed in clean, dry containers and stored in an ice bath until subsequent analysis. [28].…”
Section: Irrigation Water Samplesmentioning
confidence: 99%
“…Previous work has highlighted the environmental impacts of grazing (e.g., Vincent 2019). Grazing on federal land comes with a mix of costs, such as declines in water quality (Delrose et al 2020) and emissions (Wang et al, 2020), but may also have environmental benefits such as reductions in the risk of wildfire (Davies et al, 2016; Davies et al 2022). The coefficients reported in this paper can help further evaluate the costs and benefits of federal grazing, as well as expand to other sectors of the economy.…”
Section: Discussionmentioning
confidence: 99%